2014
DOI: 10.2147/ppa.s71666
|View full text |Cite
|
Sign up to set email alerts
|

Experience of insomnia, symptom attribution and treatment preferences in individuals with moderate to severe COPD: a qualitative study

Abstract: Persons with chronic obstructive pulmonary disease (COPD) are known to have poor sleep quality. Acceptance of and adherence to therapies for sleep problems may depend on how the person with COPD regards the source of his sleep problem, yet little is known about their attribution as to the cause of these sleep symptoms. The objective of this study was to describe the subjective sleep complaints of individuals with COPD along with their attributions as to the cause of these symptoms, and their treatment preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Being breathless and running out of oxygen without access to help led to feelings of fear and panic. 19 , 22 , 25 , 38 , 41 , 44 Patients, who had never experienced episodes of severe breathlessness, still felt anxiety and fearful, imagining future episodes of breathlessness. 11 , 30 , 34 , 38 , 49 , 57 Patients were affected by the COPD diagnosis and prognosis and the realization that they had to live with COPD for the rest of their lives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Being breathless and running out of oxygen without access to help led to feelings of fear and panic. 19 , 22 , 25 , 38 , 41 , 44 Patients, who had never experienced episodes of severe breathlessness, still felt anxiety and fearful, imagining future episodes of breathlessness. 11 , 30 , 34 , 38 , 49 , 57 Patients were affected by the COPD diagnosis and prognosis and the realization that they had to live with COPD for the rest of their lives.…”
Section: Resultsmentioning
confidence: 99%
“… 43 The inner processing was described as fear of the process of dying; the long struggle of breathlessness, struggling for air, and painful suffocation. 18 , 19 , 25 , 36 , 41 , 43 , 53 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, obstructive sleep apnea occurs frequently among individuals with ILDs, and it has been found to be significantly correlated with disease severity, including dyspnea symptoms [ 44 ]. Second, it has been reported that difficulty in falling asleep and staying asleep is accompanied by the fear of death and dying due to nighttime dyspnea in patients with COPD [ 45 ]. Cough symptoms at nighttime may compound these upsetting thoughts and, in turn, aggravate a patient’s difficulty in breathing.…”
Section: Discussionmentioning
confidence: 99%